The effects of the counseling on life style of menopausal women and - Tiznobaik, azita; mirmolaei, Tahereh; Kazemnejad, anooshiravn (Advances in Nursing & Midwifery, 2013)
Abstract Background and aim: By increasing the life expectancy, women experience longer menopause and more complications during this period of life. Men may also experience menopause. Improvement and treating the complications is based on the correcting the life style. The purpose of this study was to evaluate the effect of a counseling procedure on the life style of menopausal women and their husbands. Materials and methods: This was an interventional study. 120 couples of menopausal women and their husbands were selected from Mohammadiyeh medical health center in Hamadan participated in the study. The participants were randomly divided to control and interventional groups. Initially, life style information was collected by a questionnaire through interview. Counseling about nutritional habits and physical exercise was performed for one hour in participants’ houses. After two months there was first post test. Another counseling session and post test was performed similar to first one. Data was analyzed by Mc Nemar, Paired T test, Wilcoxon, Independent T test and Chi- square tests, using SPSS 13. Findings: Results showed a significant difference in items such as food habits and physical activities of life style, before and after of first and secondary counseling process in women and men in intervention groups (P<0.05). Conclusion: Counseling has significant effects on nutritional habits and physical activities of the menopausal women and their husbands. Counseling with couples particularly in their houses, is an effective intervention for improving of participants’ life style. Keywords: Counseling, Life style, Menopause, nutritional habits, Physical activity Corresponding Author: Azita Tiznobaik, Depart.ment of Midwifery, Faculty of Nursing and Midwifery, Coach and Member of Research Center for Child and Maternity Care, Hamadan University of Medical Sciences and Health Services, Hamadan, Iran. Email: azita.tiznobaik@umsha.ac.ir -Chiuve S Rexrode KSpiegelman D et al (2008). Primary prevention of stroke by healthy life style. American Heart Association: Circulation 118 (9) 947-54. -Collett J (2002). Promoting health among premenopausal women through Diet and Exercise. Journal of the American Academy of Nurse Practitioners. 14 (4) 172-177. -Gold E Bromberger J Crawford S et al (2001). Factor associated with age at natural menopause in a multiethnic sample of midlife women in America. American Journal Epidemiology. 53 (9) 865-874. -Harkonen K Huhtaniemi I Makinen J (2003). The polymorphic androgen receptor gene CAG repeat, pituitary-testicular function and andropausal symptoms in aging men. International Journal of Andrology. 26 (3) 187-194. -Hirvensalo M Heikkinen E Lintunen T et al (2003). The effect of advice by health care professional on increasing physical activity of older people. Scandinavian Journal of Medicine & Science in Sports. 13 (4) 231-236. -Holm A Fredrikson M (2011). More then half of the men in a Swedish people of men aged 55,65 and 75 believe in a male climactric.Aging. Male Journal.14 (1)16-20. -Jaffari Varjoushani N Anoosheh M Ahmadi F et al (2004). [Effect of family counseling on life style and blood pressure in women suffering from hypertension]. Journal of Zanjan University of Medical Sciences & Health Services. 12 (47) 23-28. (Persian). -Kerse N Elley C Robinson E et al (2005). Is physical activity counseling effective for older people? A cluster randomized controlled trial in primary care. Journal of the American Geriatrics Society. 53 (11) 1951-1956. -Lazarus J Rasch V Liljestrand J (2005). Midwifery at the crossroad in Estonia: Attitudes of midwives and other key stake holders. Acta Obstetricia et Gynecologica Scandinaviea. 84 (4) 239-48. -Magyar Z Fel T (2006). Treatment of menopausal symptoms. Review of the Current Literature. Orvosi hetilop. 147 (19) 879-885. -Nisbeth O Klausen K Andersen B (2002). Effectiveness of counseling over 1 year on changes in lifestyle and coronary heart disease risk factors. Journal of Patient Education and Counseling. 40 (2) 121- 131. -O’Halloran P Lazovich D Patterson R et al (2001). Effect of health lifestyle pattern on dietary change. American Journal Health promotion. 6 (1) 27- 33. -Polychronopoulos E Panagiotakos D Polistipioti A Diet, Life style factors and hypercholesterolemia in elderly men and women from Cyprus. Lipids in Health and Disease, 24 sep2010, vol.9:107 Published [on line]. [2 July 2012]. < http://www.biomedcentral.com/content/pdf/1476-511X-9-107.pdf -Pullen C Walker N (2002) Midlife and older rural women’s adherence to U.S. dietary guidelines across stages of change in healthy eating. Journal of Public Health Nursing. 19 (3) 170-178. -Rasooli F Haj Amiry P Mahmoodi M et al ( 2002) Assessment of the application for preventive factors of osteoporosis, in menopausal women referred to the health care centers in Tehran University of Medical Sciences. Hayat. The Journal of Faculty of Nursing & Midwifery. 8 (2) 4-11. (Persian). -Rozenbaum H (1998). Why has menopause become a public health problem. Therapei. 53 (1) 49-59. -Steptoe A Doherty SH Rink E et al (1999). Behavioral counseling in general practice for the promotion of healthy behavior among adults at increased risk of coronary heart disease: Randomized trial. British Medical Journal. 319(7215) 943-994. -Taechakraichana N Jaisamaram U Panyakhamlerd K et al (2002). Climacteric: Concept consequence and care. Journal of the Medical Association Thailand. 85 suppl 1:S1-15. -White M (1993). The New Castle Health and lifestyle survey 1991: user manual. Newcastle- upon- tyne, Newcastle Health Authority and university of new-castle.<http://www.ncl.ac.uk/ihs/research/publichealth. -Woollard J Beilin L Lord T et al (1995). A controlled trial of nurse counseling on lifestyle change for hypertensive treated in general practice: preliminary results. Journal Clinical and Experimental Pharmacology & Physiology. 22 (6-7) 466- 468.